Packaging the presidency : a history and criticism of presidential campaign advertising - Jamieson, Kathleen Hall (Oxford scholarship online, 2023)
"If political advertising did not exist, we would have to invent it," writes Katherine Hall Jamieson in her widely praised study, Packaging the Presidency. Now in a new third edition, Jamieson expands her authoritative analysis of political advertising, looking at the media campaigns of American presidents from the early days of the republic to the successful 1992 Clinton campaign. Chronicling the evolution of the campaign ad from political songs and slogans through handbill and newspaper cartoon to radio and television coverage, an argument emerges that is subtle but persuasive: though often equivocal, and even downright sleazy, political advertising is vital in reminding voters of the choices at the heart of democracy. Much of the book, appropriately, focuses on the powerful media campaigns of the post-war period. In individual chapters devoted to presidential campaigns since 1952, the claims of media strategists, campaign memos, and journalists frame discussions on the impact of candidates from Adlai Stevenson, Richard Nixon, John F. Kennedy, and Ronald Reagan to the country's more recent high-profile and media savvy candidates such as Ross Perot and Bill Clinton. This new edition covers such issues as the new forms of exposition due to increased access created by cable that so powerfully impacted the 1992 campaign. The wide variety of venues, including MTV and the Nashville Network, coupled with almost daily appearances on morning talk shows, afforded candidates the ability to reach audiences by the millions in "news-ads" that served as free extended commercials. Jamieson points out the success of Ross Perot's unconventional revival of the thirty-minute program spot, an important innovation that reflected both the power of modern-day "infomercial" and marked a radical change in political strategist's ideas of the viewing electorates response
Keywords: Presidents : United States : Election; Advertising, Political : United States; United States : Politics and government : 1945-1989; United States : Politics and government : 1989-